Engineering Interventions in Foods and Plants - Verma, Deepak Kumar; Goyal, Megh R. (Apple Academic Press, 2017)
"With contributions from a broad range of leading professors and scientists, this volume focuses on new areas of processing technologies in foods and plants to help meet the increasing food demand of the rapidly growing populations of the world. The first section of the book is devoted to emerging entrepreneurship and employment opportunities for rural peoples in food and agricultural processing, specifically beekeeping technology and honey processing; herbal formulations for treatment of dental diseases; and engineering interventions for the extraction of essential oils from plants. Part 2 contains three chapters that discuss technological interventions in foods and plants for human health benefits, looking particularly at coffee, tea, and green leaf vegetable processing technology. The volume goes to look at several management strategies in agricultural engineering, with a chapter on production technology of ethanol from various sources and its potential applications in various industries, including chemical, food, pharmaceutical as well as biofuel. Food grain storage structures are addressed as well, focusing on minimizing losses from microbial pests as well as insect pests during grain storage by utilizing different efficient storage structures The volume provides a valuable resource for students, instructors, and researchers of foods and plants processing technology. In addition, food and plant science professionals who are seeking recent advanced and innovative knowledge in processing will find this book helpful. "--Provided by publisher.
part Part i: emerging entrepreneurship for rural areas -- chapter 1 beekeeping technology and honey processing: emerging entrepreneurship for rural areas / Vishal Singh -- chapter 2 herbal formulations for treatment of dental diseases: perspectives, potential and applications / Ashwini G. Patil -- chapter 3 engineering interventions for extraction of essential oils from plants / Saad Rehman Saeed Al-Hilphy -- part Part ii: engineering interventions in foods and plants for health benefits -- chapter 4 processing technology and potential health benefits of coffee / Vishal Singh -- chapter 5 biochemical composition, processing technology and health benefits of green tea: a review / Vishal Singh -- chapter 6 effects of thermal processing on nutritional composition of green leafy vegetables: a review / Deepak Kumar Verma -- part Part iii: management strategies in agricultural engineering -- chapter 7 ethanol production from different substrates: effects on environmental factors and potential applications / Leela Wati -- chapter 8 food grain storage structures: introduction and applications / Vishal Singh.
Keywords: Agricultural processing; Food -- Technological innovations; Plant products -- Technological innovations; TECHNOLOGY & ENGINEERING -- Agriculture -- General; TECHNOLOGY & ENGINEERING -- Food Science; Agriculture; AGRICULTUREnetBASE; FOODnetBASE; Product Development; SCI-TECHnetBASE; STMnetBASE